POLICIES TO REDUCE AND PREVENT HOMELESSNESS: WHAT WE KNOW AND GAPS IN THE RESEARCH. (2nd February 2021) - Evans, William N.; Phillips, David C.; Ruffini, Krista
Abstract: Homelessness may be both a cause of and one of the more extreme outcomes of poverty. Governments at all levels and private organizations have a variety of tools to combat homelessness, and these strategies have changed dramatically over the past quarter century. In this paper, we catalog the policy responses and the existing literature on the effectiveness of these strategies, focusing on studies of individual‐level effects from randomized controlled trial evaluations and the best quasi‐experimental designs. We conclude by discussing outstanding questions that can be addressed with these same methods.